Sustainability in supply chains: A content analysis of sustainability reports in the brewing industry - Sundgren, Caroline (My University, 2015)
This study examines how the concept of sustainability has been addressed in research and in practice. First, a literature review is conducted in order to assess what fields have addressed the concept of sustainability and to identify trends. Secondly, the main themes with respect to the sustainability and the supply chain are derived a sample of articles published in journals ranked 3-4 by the ABS association. The brewing industry has been selected as unit of analysis for the case study. A content analysis is made on sustainability reports from 2013 of the eights case companies (AB InBev, SABMiller, Heineken, Carlsberg, Tsingtao Brewery Group, Molson-Coors, Efes Group and Grupo Mahou - San Miguel). In this context, the general reporting practices are discussed and the main indications which the firms have disclosed are identified. The findings suggest that sustainability is a topic that is increasingly receiving more attention and has become mainstream. The results are supported both from the perspective of literature and when reporting practices have been analyzed in the brewing industry. Furthermore, the common theme derived from literature and from the reports was governance over suppliers.
Keywords: Sustainability; Supply Chain; Sustainability Reporting; fi=Master's Degree Programme in Strategic Management|